Effects of intracoelomic transmitter implantation on metabolic rate, swimming performance, growth and survival in juveniles of two salmonids. Issue 4 (5th August 2019) - Darcy, Andrew P.; Raby, Graham D.; Johnson, Timothy B.; Pitcher, Trevor E.; Fisk, Aaron T.
Abstract: In this study, we investigated the effects of acoustic tag implantation on standard and routine metabolic rate (SMR and RMR, estimated via oxygen consumption), critical swimming speed ( U crit ), survival and growth in juveniles of rainbow trout Oncorhynchus mykiss and lake trout Salvelinus namaycush . Tag burdens ranged from 1.8% to 7.5% across the two species. Growth rates in acoustic‐tagged fish were equal to or higher than those in other treatments. Acoustic‐tagged S. namaycush had a marginally lower U crit than controls but that effect was not replicated in the O. mykiss experiment. Tagging did not have clear effects on metabolic rate but there was an interaction whereby SMR and RMR tended to increase with time since surgery in tagged O. mykiss but not in other treatments (the same trend did not occur in S. namaycush ). Survival was high across treatments (mean 98% survival among O. mykiss, 97.5% among S. namaycush ). There were no statistically significant effects of tag burden (percentage of body mass) except for a weak negative relationship with growth rate (across species) and a weak positive relationship with U crit but only in the O. mykiss . Collectively, our findings suggest there were minor, context‐dependent effects of acoustic tagging in juvenile S. namaycush and O. mykiss during an eight‐week laboratory experiment. Further research will be required to assess whether tagging can cause meaningful behavioural effects in these species in captivity or in the wild and whether there is a tag burden threshold above which deleterious effects consistently occur.